Hubungan Antara Nutrisi Dan Kecerdasan Emosional Pada Anak Usia Dini - Riza Wahyu Utami (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2023)
Food is a basic human need, which requires accuracy and caution in choosing daily food. The success of implementing an early childhood feeding program to meet nutritional needs is very dependent on the role of parents. Parents must have skills and knowledge in processing food and managing children's nutrition. So that the development of the child's level of emotional intelligence is achieved perfectly. Providing healthy food to children is the main support in fulfilling nutrition in the growth process and level of social-emotional development. The aim of this research was to find out how the pattern of providing food is in order to build emotional intelligence in early childhood. Providing balanced nutritious food for children will increase emotional intelligence in optimizing the learning process because it can increase enthusiasm and concentration in class. Every child has different nutritional needs and it depends on their activity level, height, weight and immunity. One difference can be seen based on the activity between active and passive children so that calorie needs are certainly different when children do activities.